PENGARUH METODE PELATIHAN KERJA TERHADAP PENINGKATAN KETERAMPILAN PRAMUSAJI FOOD & BEVERAGE SERVICE SWISS-BELHOTEL HARBOUR BAY BATAM - Yuki Lusiana Eka; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to determine how the influence of the training methods work towards food and beverage service waitress skill enhancement at Swiss-Belhotel Harbour Bay Batam.This research uses descriptive quantitative method for examining the issues raised. The sample in this research are 18 people and using census method. While the data collection techniques in this research using questionnaires, observation and documentation. By using a Likert scale as a measure to determine the length of the interval, multiple linear regression analysis, content validity test, reliability test and a test of hypothesis to determine the correlation between x and y.Based on the research that has been done, there is a significant relationship or correlation between the training method to increase waitress skills. The more often it does, the job training methods will increasingly influence the improvement of food and beverage service waitress skills at Swiss-Belhotel Harbour Bay Batam.Keywords: Training Methods, Skills Improvement, Swiss-Belhotel Harbour Bay Batam